Estimating real-time infiltration for use in residential ventilation control. Issue 4 (April 2020) - Ng, Lisa C.; Zimmerman, Stephen; Good, Jeremy; Toll, Brian; Emmerich, Steven J.; Persily, Andrew K.
Minimum outdoor air ventilation rates specified in standards such as ASHRAE Standard 62.2–2016 are generally based on envelope airtightness, building floor area, geographical location and number of occupants. ASHRAE Standard 62.2–2016 allows for a constant infiltration credit, which reduces the required mechanical ventilation. However, infiltration rates vary based on the weather and system operation. Thus, mechanical systems could potentially operate less if the real-time (RT) infiltration rate was known and used to adjust the mechanical ventilation rate. CONTAM models of two test houses on the campus of the National Institute of Standards and Technology were verified with measurements and used to simulate hourly infiltration rates in three cities. The infiltration rates were passed to a theoretical controller that changed the hourly mechanical ventilation rate to meet the ventilation requirement. Simulated energy use and relative annual occupant exposure for this RT control strategy were compared with ventilation at a constant rate. Implementation of the RT control strategy resulted in annual average energy savings of $66USD across both houses and three cities without increasing the annual occupant exposure compared with ventilating continuously at a constant rate. The authors discuss the advantages and limitations of the proposed RT ventilation control strategy.